Tracing the Earliest Stages of Star and Cluster Formation in 19 Nearby Galaxies with PHANGS-JWST and HST: Compact 3.3 μm Polycyclic Aromatic Hydrocarbon Emitters and Their Relation to the Optical Census of Star Clusters - M. Jimena Rodríguez; Janice C. Lee; Remy Indebetouw; B. C. Whitmore; Daniel Maschmann; Thomas G. Williams; Rupali Chandar; A. T. Barnes; Oleg Y. Gnedin; Karin M. Sandstrom; Erik Rosolowsky; Adam K. Leroy; et al. (The Astrophysical Journal)
The earliest stages of star and cluster formation are hidden within dense cocoons of gas and dust, limiting their detection at optical wavelengths. With the unprecedented infrared capabilities of JWST, we can now observe dust-enshrouded star formation with ∼10 pc resolution out to ∼20 Mpc. Early findings from PHANGS-JWST suggest that 3.3 μ m polycyclic aromatic hydrocarbon (PAH) emission can identify star clusters in their dust-embedded phases. Here, we extend this analysis to 19 galaxies from the PHANGS-JWST Cycle 1 Treasury survey, providing the first characterization of compact sources exhibiting 3.3 μ m PAH emission across a diverse sample of nearby star-forming galaxies. We establish a selection criteria based on a median color threshold of F300M − F335M = 0.67 at F335M = 20 and identify 1816 sources. These sources are predominantly located in dust lanes, spiral arms, rings, and galaxy centers, with ∼87% showing concentration indices (CIs) similar to optically detected star clusters. Comparison with the PHANGS-HST catalogs suggests that PAH emission fades within ∼3 Myr. The H α equivalent width of PAH emitters is 1–2.8 times higher than that of young PHANGS-HST clusters, providing evidence that PAH emitters are on average younger. Analysis of the bright portions of luminosity functions (which should not suffer from incompleteness) shows that young dusty clusters may increase the number of optically visible ≤3 Myr old clusters in PHANGS-HST by a factor between ∼1.8× and 8.5×.